Aerosol analysis using quantum cascade laser infrared spectroscopy: Application to crystalline silica measurement. (December 2020) - Wei, Shijun; Kulkarni, Pramod; Zheng, Lina; Ashley, Kevin
Abstract: A method for trace analysis of aerosol mineral components using quantum cascade laser (QCL) based infrared absorption spectroscopy is described. The measurement approach involves: (a) collection of aerosol on a particulate filter; (b) sample treatment using low-temperature oxygenated plasma to minimize the matrix interferences; (c) redeposition of the treated sample as a dried spot for direct-on-filter analysis; and (d) infrared transmittance measurement of the dried spot using the QCL and mercury-cadmium-telluride detector. The method was applied to quantification of trace α-quartz in workplace aerosols. Infrared absorbance spectra in the range 750–1030 cm −1 were obtained using the QCL instrument; the characteristic peak of α-quartz at 798 cm −1 was used to measure its content. A correction scheme was applied to account for spectral interference from kaolinite mineral for coal dust samples. The detection limit for α-quartz was estimated to be 0.12 μg for a dried spot diameter of 1 mm. This detection limit is an order-of-magnitude lower than those attainable by the current standard X-ray diffraction (XRD) or Fourier transform infrared spectroscopy (FTIR) methods involving similar sample preparation and treatment. The QCL method was extended to the measurement of respirable α-quartz concentrations in workplace aerosols released during cutting of fiber-reinforced cement and engineered stone products (used in building construction), as well as those from various coal mine dusts. The measurements compared well with those from the standard XRD method, even for samples with matrix and mineral interferences. The results show that QCL-based IR transmission spectroscopy can offer sensitive, trace-level measurement of aerosol mineral components. Highlights: Method for aerosol chemical analysis using quantum cascade laser. Sample preconcentration as dried spot allows superior sensitivity and precision. Detection limits of α-quartz <<1 μg/m 3 can be achieved.